2017
DOI: 10.1371/journal.pone.0175842
|View full text |Cite
|
Sign up to set email alerts
|

SPR-based fragment screening with neurotensin receptor 1 generates novel small molecule ligands

Abstract: The neurotensin receptor 1 represents an important drug target involved in various diseases of the central nervous system. So far, the full exploitation of potential therapeutic activities has been compromised by the lack of compounds with favorable physicochemical and pharmacokinetic properties which efficiently penetrate the blood-brain barrier. Recent progress in the generation of stabilized variants of solubilized neurotensin receptor 1 and its subsequent purification and successful structure determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Fragments from primary FBDD screens typically bind to their targets in the micromolar to millimolar range [ 26 ]. For example, in a study of neurotensin I, the compounds identified had K D values between 18 and 400 μM [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fragments from primary FBDD screens typically bind to their targets in the micromolar to millimolar range [ 26 ]. For example, in a study of neurotensin I, the compounds identified had K D values between 18 and 400 μM [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of these variables, we have some control over the protein immobilization level; however, the NSB problem is more readily attenuated by keeping the compound concentration low. A survey of published SPR FBS conditions 42,[52][53][54] reveals that many users are opting to screen at fragment concentrations of <300 µM in order to combat the problem of NSB. Although it might attenuate NSB, low-concentration SPR fragment screening limits the fragment binding affinity range that is detectable.…”
Section: Screening Concentration and Nsbmentioning
confidence: 99%
“…More detail on the configuration and analysis of SPR competition experiments can be found in the following references. [54][55][56]…”
Section: Competition Sprmentioning
confidence: 99%
“…Thus, improved screening assays are an important component of the discovery of novel compounds. Alternatively, SPR has been used to screen 6,369 compounds as potential GPCR ligands (neurotensin receptor 1) [8].…”
Section: Expert Opinionmentioning
confidence: 99%